Comparison of the microhardness of composite resin with conventional and modified index techniques with printed cuvette in two light-curing times - Santos-Busso, Alfonso Napoleón (2024)
Objective: To compare the microhardness of composite resin with conventional and modified index techniques with a printed tray in two light cures. Materials and methods: There were six study groups according to the technique and the number of photopolymerizations: direct technique with one photopolymerization (D1F), direct with two photopolymerizations (D2F), conventional index with one photopolymerization (IC1F), conventional index with two photopolymerizations (IC2F), modified index with one photopolymerization (IM1F), modified index with two photopolymerizations (IM2F). Fifteen samples were used for each group. The samples had dimensions of 2 mm in height by 5 mm in diameter. The photopolymerization was performed following the indications of the group to which it corresponds and then subjected to the Vickers hardness test with three indentations on each side with a load of 200 g for 15 seconds. Two microhardness recordings were made, one superficial and the other at 2 mm. Results: There is a significant difference between the first light-curing surface microhardness groups (p < 0.001), and there is also a significant difference between the first light-curing 2 mm microhardness groups (p < 0.001). Likewise, there are no significant differences between the second light-curing surface microhardness groups (p = 0.519) or the second light-curing 2 mm microhardness groups (p = 0.279). Conclusions: There are no significant differences in surface microhardness and microhardness at 2 mm depth with conventional and modified index techniques in printed trays in two photopolymerizations.